ON METROLOGICAL EVALUATION OF ACOUSTIC EMISSION METHOD AS TOOL OF POROUS MATERIALS IMPREGNATION CONTROL - Vladimir L. Gaponov; Dmitry M. Kuznetsov; Ekaterina S. Cherunova; Maria S. Zakharova (Advanced Engineering Research, 2012)
The possibility of using the acoustic emission (AE) method to stud y the impregnation processes of the woven fabric is considered. In particular, it is found that the total AE curve irrespective of the sample size ca n be depicted by the general equation. The relaxation response time for the woven fabric is deduced from ex periments.